Augmented cement shelf acetabuloplasty to improve hip stability in elderly patients with recurrent hemiarthroplasty dislocations - Rajul Gupta; Evan Dowell; Toan Theodore Le (Journal of Orthopaedics, Trauma and Rehabilitation)
Background The treatment of dislocated hip hemiarthroplasty in low-demand elderly patients is controversial due to poor results with closed reduction, and significant complications with exchange arthroplasty. This case series demonstrates the use of a novel, simple surgical technique for hip hemiarthroplasty containment without resorting to exchange arthroplasty. Methods Eleven patients where screw-augmented cement shelf acetabuloplasty procedures were performed were retrospectively identified. All surgeries were performed by a single attending surgeon, at a level-one trauma center, from 2015 to 2022. Previous dislocations, interventions, co-morbidities, mobility level, and posterior wall deficiency were recorded from the patient's charts. The following outcome measures were recorded: operative time, blood loss, perioperative complications, early and late infections, shelf loosening, subsequent dislocations, and the need for additional procedures. Results The median duration between hip hemiarthroplasty and shelf procedure was 56 days. The mean duration of the surgical procedure was only 63 min, and the mean blood loss was only 250 mL. There was only one instance of loosening of the cement shelf. Two patients had surgical site infections leading to sepsis and death. In two patients, the femoral head was exchanged to improve stability. All patients were allowed immediate weight bearing after the procedure. Conclusions Shelf acetabuloplasty is a simple, inexpensive, and safe procedure to salvage recurrent hip hemiarthroplasty dislocation in low-demand patients. Shorter surgical duration, relatively lower blood loss, and immediate weight bearing render this an attractive procedure for this fragile population.